2019
DOI: 10.1002/hed.25594
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between plan quality improvements and reduced acute dysphagia and xerostomia in the definitive treatment of oropharyngeal squamous cell carcinoma

Abstract: Background To evaluate plan quality using volumetric‐modulated arc therapy (VMAT) and step‐and‐shoot intensity‐modulated radiation therapy (SS‐IMRT) techniques and for patients treated for oropharyngeal squamous cell carcinoma (OPSCC). Methods Treatment plans for patients treated definitively for stages I‐IVb, OPSCC between December 2009 and August 2015 were retrospectively reviewed. Dosimetric endpoints of involved organs‐at‐risk (OARs) were retrieved from clinical plans. Common Terminology Criteria for Adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
2
7
0
2
Order By: Relevance
“…Compared with IMRT, we found that VMAT was better at preventing Xer2y. This finding supported the previous work [ 19 ]. Furthermore, we revealed that VMAT conserves salivary function when coMD is established.…”
Section: Discussionsupporting
confidence: 94%
“…Compared with IMRT, we found that VMAT was better at preventing Xer2y. This finding supported the previous work [ 19 ]. Furthermore, we revealed that VMAT conserves salivary function when coMD is established.…”
Section: Discussionsupporting
confidence: 94%
“…All the treatment plans were dosimetric compared. In the group of patients irradiated by VMAT technique, the toxicities were signifi cantly lower 7 .…”
Section: Intensity Modulated Volumetric Therapy (Vmat) In Hnsccmentioning
confidence: 91%
“…AP has been extensively used for various sites in our department with consistently reasonable results. The AP optimization objectives used in this study were determined based on our prior experience in planning and treating for OPSCC [ 10 , 11 ]. To achieve consistent dosimetric qualities, both plans were optimized with the same set of objectives without any manual adjustment to eliminate any planner bias.…”
Section: Methodsmentioning
confidence: 99%